RNAs That Behave Like Prions - Arcady R. Mushegian (American Society for Microbiology, 2020)
ABSTRACT The term “prion” was originally coined to describe the proteinaceous infectious agents involved in mammalian neurological disorders. More recently, a prion has been defined as a nonchromosomal, protein-based genetic element that is capable of converting the copies of its own benign variant into the prion form, with the new phenotypic effects that can be transmitted through the cytoplasm. Some prions are toxic to the cell, are able to aggregate and/or form amyloid structures, and may be infectious in the wild, but none of those traits are seen as an integral property of all prions. We propose that the definition of prion should be expanded, to include the inducible transmissible entities undergoing autocatalytic conversion and consisting of RNA rather than protein. We show that when seen in this framework, some naturally occurring RNAs, including ribozymes, riboswitches, viroids, viroid-like retroelements, and PIWI-interacting RNAs (piRNAs), possess several of the characteristic properties of prions.